Firm size, Age, Industrial Networking, and Growth: A Case of the Korean Manufacturing Industry - Park, Younsuk; Shin, Jaeun; Kim, Taejong (SMALL BUSINESS ECONOMICS, 2010)
This paper investigates the roles of firm size, age, and industrial networking in determining firm growth. Analyses using the 2-year panel data of 7,889 Korean manufacturing firms between 1994 and 2003 confirm that firm size and age have significant negative effects on firm growth and significant positive impacts on firm survival. R&D and export activities are found to facilitate both firm growth and survival. The primary focus of this study is to examine the effects of industrial networking, such as subcontracting and clustering, on firm growth. The results show that subcontracting does not yield any positive effect for firm growth, but encumbers survival, which may be accounted for by the high subcontracting intensity among small firms. Clustering, on the other hand, is found to promote firm growth and survival. There is, however, little evidence that such a positive effect of clustering is derived from network externalities through cooperation and competition among firms in a cluster per se.
Keywords: RESEARCH-AND-DEVELOPMENT; HIGH-TECHNOLOGY FIRMS; GIBRATS-LAW; EMPIRICAL-ANALYSIS; SERVICES; SURVIVAL; CLUSTERS; PLANTS; TESTS; PANEL